La sensibilidad humana. Su presencia en las cartas de José Martí de 1895. (2017)
The theoretical basis of the text lies in the urgency of humanity to fight for the enrichment of the spiritual universe and against indifference to problems. It develops two thematic nuclei related to each other: one, the category human sensitivity, which offers considerations and features, such as the feeling-reason conjugation and the emission of responses to the stimuli; two, the presence of this category in the letters that the Cuban thinker and patriot Jose Marti (1853-1895) writes during 1895.